Sex-Specific Association Between Socioeconomic Status, Lifestyle, and the Risk of Frailty Among the Elderly in China - Wang, Huai-yu; Zhang, Mufan; Sun, Xiaojing (Frontiers in Medicine, 2021)
Background Lifestyle contributors to frailty among the elderly were previously reported in developed Western countries, while evidence from the less developed East Asian regions was still lacking. Due to the well-acknowledged sex-based disparity of frailty and sex-difference of socioeconomic status and lifestyle, it is worth investigating the sex-specific association between social and behavioral contributors and the risk of frailty among the East Asian longevous population. Methods The present study was an observational study based on four waves of interviews of the Chinese Longitudinal Healthy Longevity Surveys (CLHLS) from 2008 to 2018. Participants aged ≥ 65 years and without frailty at baseline were included. Fried criteria (exhaustion, shrink, weakness, low mobility, inactivity) were adopted to identify the incidence of frailty (≥3 domains) and pre-frailty (1-2 domains) during the follow-up. The sex-specific association between lifestyle (smoke status, drinking status, food intake, sleep, exercise, physical activity) and the risk of incident pre-frailty and frailty was analyzed using multinomial logistic regression models. Results Altogether, 3,327 participants aged 81.2±10.3(range 65-116) years were included. In total, 964(29.0%) and 1,249(37.5%) participants were recognized as having incident pre-frailty and frailty, respectively. Older females were disproportionately uneducated, frequently did housework and labor work, but seldom did exercise. Males had diverse dietary and recreational activities, but frequently exposed to tobacco and alcohol. The protective effects of higher income, exercise, doing housework and daily intake of fresh fruits/vegetables were found in both sexes. (P<0.05) Sleep disorders (odds ratio[OR]=2.16, 95% confidence interval [CI] 1.28-3.62) and labor work (OR=2.18, 95%CI 1.42-3.33) were associated with the increased risk of frailty among females. For males, diverse dietary (4 types of food added: OR=0.21, 95%CI 0.09-0.50) showed protective effect on the risk of frailty, but daily intake of pickled vegetables showed the opposite effect (OR=1.86, 95%CI 1.12-3.07). Conclusions Socioeconomic status, lifestyle and the association with the risk of frailty showed substantial difference between sexes among the longevous population in China. To establish the individualized strategy of behavioral improvement for frailty prevention should consider the sex-disparity.